Addition of terminal alkynes to α-ketone esters to synthesize α-tertiary-hydroxy esters promoted by zinc and an alkyl halide. Issue 46 (18th November 2015) - Zhang, Wen; Cao, Yuan; Chen, Wei; Zhao, Gang; Pu, Lin
Graphical abstract: Abstract: A convenient method to synthesize various α-tertiary-hydroxy esters at room temperature has been developed. This method uses the readily available and inexpensive Zn powder in combination with an alkyl halide to promote the addition of alkynes to α-ketone esters with no need to exclude air or moisture. It has also been extended to promote the reaction of alkynes with a variety of aldehydes and other electron-deficient ketones.